2023
DOI: 10.1093/annweh/wxac087.130
|View full text |Cite
|
Sign up to set email alerts
|

61 Evaluation of the Toxicity, Alveolar Cell Accumulation and Clearance of PET and PS Nanoplastics in Mouse Lungs

Abstract: Airborne micro and nano-plastics (MNPs) have been detected in both indoor and outdoor settings, raising concerns about potential adverse effects upon inhalation. Yet, their potential pulmonary toxicity has not been studied extensively. Herein, we evaluated the pulmonary toxicity and clearance of nanometric Poly-Ethylene Terephthalate (PET; ~50-200 nm) fragments from plastic bottles and two nanometric polystyrene (PS; 50 and 200 nm) beads. Adult mice were exposed to a unique dose of 50 ug in 30uL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They perhaps move throughout the body using systemic blood and lymphatic routes to evade organs, tissues and, ultimately the cells. [11,12] Studies have also substantiated their ability to transcend the blood-brain barrier, the highest reach a molecule can have inside a body. [7,13] Studies on Caenorhabditis elegans with polystyrene micro and nanoplastics indicated nanoplastics are more readily uptaken by the organisms.…”
Section: Introductionmentioning
confidence: 99%
“…They perhaps move throughout the body using systemic blood and lymphatic routes to evade organs, tissues and, ultimately the cells. [11,12] Studies have also substantiated their ability to transcend the blood-brain barrier, the highest reach a molecule can have inside a body. [7,13] Studies on Caenorhabditis elegans with polystyrene micro and nanoplastics indicated nanoplastics are more readily uptaken by the organisms.…”
Section: Introductionmentioning
confidence: 99%